Zodiacal light observations and its link with cosmic dust: A review. (1st October 2020) - Lasue, Jeremie; Levasseur-Regourd, Anny-Chantal; Renard, Jean-Baptiste
Abstract: The zodiacal light is a nightglow mostly visible along the plane of the ecliptic. It represents the background radiation associated with solar light scattered by the tenuous flattened interplanetary cloud of dust particles surrounding the Sun and the planets. It is an interesting subject of study, as the source of the micrometeoroids falling on Earth, as a link to the activity of the small bodies of the Solar System, but also as a foreground that veils the low brightness extrasolar astronomical light sources. In this review, we summarize the zodiacal light observations that have been done from the ground and from space in brightness and polarization at various wavelength ranges. Local properties of the interplanetary dust particles in some given locations can be retrieved from the inversion of the zodiacal light integrated along the light-of-sight. We show that the current community consensus favors that the majority of the interplanetary dust particles detected at 1 au originate from the activity of comets. Our current understanding of the interplanetary dust particles properties is then discussed in the context of the recent results from the Rosetta rendezvous space mission with comet 67P/Churyumov-Gerasimenko.